2017
DOI: 10.1128/mbio.00897-17
|View full text |Cite
|
Sign up to set email alerts
|

On the Origin of Reverse Transcriptase-Using CRISPR-Cas Systems and Their Hyperdiverse, Enigmatic Spacer Repertoires

Abstract: Cas1 integrase is the key enzyme of the clustered regularly interspaced short palindromic repeat (CRISPR)-Cas adaptation module that mediates acquisition of spacers derived from foreign DNA by CRISPR arrays. In diverse bacteria, the cas1 gene is fused (or adjacent) to a gene encoding a reverse transcriptase (RT) related to group II intron RTs. An RT-Cas1 fusion protein has been recently shown to enable acquisition of CRISPR spacers from RNA. Phylogenetic analysis of the CRISPR-associated RTs demonstrates monop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
90
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
2
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(100 citation statements)
references
References 57 publications
(75 reference statements)
7
90
1
Order By: Relevance
“…It has even been suggested that the first CRISPR/Cas system could have been used for targeting transposition with ancient casposon elements, a process that later re‐evolved with Tn7‐like elements (Koonin and Makarova, ). In another example of exchange, spacer acquisition in one subtype within the type III CRISPR/Cas systems gained the capacity to harvest spacer information from RNA through the apparent capture of reverse transcriptase activity from Group II introns (Silas et al , ; Silas et al , ). Finally, the Cas12 effector proteins of type V CRISPR/Cas systems appears to have been derived from a RuvC‐like nuclease activity from IS605‐like transposons on multiple occasions (Koonin and Makarova, ).…”
Section: Other Evolutionary Relationships Between Crispr/cas Systems mentioning
confidence: 99%
“…It has even been suggested that the first CRISPR/Cas system could have been used for targeting transposition with ancient casposon elements, a process that later re‐evolved with Tn7‐like elements (Koonin and Makarova, ). In another example of exchange, spacer acquisition in one subtype within the type III CRISPR/Cas systems gained the capacity to harvest spacer information from RNA through the apparent capture of reverse transcriptase activity from Group II introns (Silas et al , ; Silas et al , ). Finally, the Cas12 effector proteins of type V CRISPR/Cas systems appears to have been derived from a RuvC‐like nuclease activity from IS605‐like transposons on multiple occasions (Koonin and Makarova, ).…”
Section: Other Evolutionary Relationships Between Crispr/cas Systems mentioning
confidence: 99%
“…Moreover, these work seeded on known CRISPR-Cas loci, and thus would not have looked at the locus described here. The spacer sequences here (Fig 1a) could not identify any known organism, echoing the observation that 'the vast majority of RT-linked CRISPR spacers come from a distinct sequence pool, the nature of which remains enigmatic' [29].…”
Section: Reverse Transcriptase Based Crispr Locimentioning
confidence: 61%
“…In many Type III CRISPR systems, a reverse transcriptase (RT) is fused to a Cas1, which in the marine bacterium Marinomonas mediterranea, was shown to mediate the in vivo acquisition of RNA spacers [28]. Two recent studies looked at the evolutionary origins of RT-CRISPR, and looked mostly at RT-Cas1 fusions [29,30]. Moreover, these work seeded on known CRISPR-Cas loci, and thus would not have looked at the locus described here.…”
Section: Reverse Transcriptase Based Crispr Locimentioning
confidence: 99%
See 2 more Smart Citations